THE PSYCHOLOGICAL IMPACT OF SURVIVORS OF THE EARTHQUAKE, TSUNAMI, AND LIQUEFACTION: A QUALITATIVE STUDY - Arifah, Nur; Ismunandar, Ismunandar; Gustini; Sukmawati; Yuwono, Dian Kurniasari; Galenso, Nitro; Pangaribuan, Helena (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2024)
Introduction: Natural disasters in the form of earthquakes, tsunamis, and liquefactions in Central Sulawesi in 2018 had several impacts on disaster survivors' psychology. These psychological problems have developed as an effect from serious injuries or loss of family members of the survivors. Psychological disorders, such as anxiety, depression, to Post traumatic stress disorder, can affect long-term quality of life. This study aims to explore the psychological impacts experienced by survivors of the earthquake, tsunami, and liquefaction in Central Sulawesi. Method: A qualitative study with a phenomenological approach. In-depth interviews were conducted using semi-structured guideline, observation and voice recording of 18 survivors of the earthquake, tsunami, and liquefaction disasters. The determination of the sample is using a purposive sampling technique based on inclusion criteria. The results of the interviews were transcribed, member checking, and analyzed using the Van Mannen method. Results: This study produced four themes and fifteen sub-themes. The research themes consist of the grieving phase, post-traumatic stress disorder, social support and health services support. Conclusions: Further screening of disaster survivors who experienced psychological disorders is needed, not only as a preventive measure but also as a psychological support to improve their quality of life.